PENANGGULANGAN KEMISKINAN MELALUI PUSAT KESEJAHTERAAN SOSIAL DALAM PERSPEKTIF PELAYANAN PUBLIK - Rohman, Abd.; Sukiman, Antonius; Trihardianto, Willy (Universitas Panca Marga, 2021)
Poverty is an urgent national problem and it requires systematic handling steps. This study had purpose to analyze poverty alleviation efforts through the Social Welfare Center (Puskesos) from the perspective of public services. This study used descriptive qualitative method. The data included primary and secondary data and the collecting data used interviews, observation and documentation. Informants determined by using purposive sampling. Data analysis used Miles & Huberman model, that's data reduction, presentation, making conclusions and verification. Validity of the data used triangulation techniques. The results showed that the implementation of Integrated Database services (BDT) through the Social Welfare Center (Puskesos) had run optimally. This is proven by good administrative services, goods, and servicing the poor society from the process of providing goods, preparation, to the proposals. This service implementation is supported and in collaboration with social strength at the RT / RW level, social cadres, employee and village facilitators. The management of mechanism and registration are done by giving information to the society about the programs, procedures, and requirements that must be completed. Then, This data becomes the government's reference for processing data verification and validation in determining the poor society who have a right to receive the facilities will be given. The obstacles of this implementation are services such as access to distant of part area, networks, BDT processor programs, and society's apathy in completing requirements. So, it needs commitment and principle of picking up the village government by involving social cadres and youth cadets who have been given training to provide assistance to the poor society. Keywords: Poverty, social welfare, service